Analysis and optimization of energy release and fuel burnup nonuniformity in the WWER-1000 fuel assembly - A. A. Lapkis; A. S. Starchenko; D. V. Trishechkin; I. Yu. Popova (Глобальная ядерная безопасность, 2023)
The paper considers and systematises the options of fuel assemblies (FAs) for the WWER-1000 reactor. In the Serpent neutron-physics code, an infinite-height fuel assembly with six fuel pins is modelled using the U49G6 pattern used in the WWER-1000 «large series» fuel assemblies. Variants of fuel elements placement with lower non-uniformity of energy release on fuel assemblies were selected as a result of calculations, and the influence of the number of fuel elements and their placement on reactivity was evaluated.  It is shown that gadolinium fuel elements placement in the fourth ring is optimal from the point of view of non-uniformity of fuel energy release and burn-up depth. The influence of the fuel assembly layout on the fuel burnup depth for separate groups of fuel pins is considered. The variant of reduction of computational resources expenditures by means of allocation of the most different in energy release and burnup groups of gadolinium fuel rods is offered. Comparison of the investigated assemblies with the existing U49G6 type fuel assembly is carried out. A method to estimate the underproduction of thermal energy in the fuel assembly associated with the non-uniformity of fuel element burnup in it, while maintaining the maximum burnup depth for individual fuel elements at the level of existing samples is proposed. On the basis of the analysis of the value of underproduction, a variant of improving the configuration of fuel assemblies with six fuel elements is proposed to equalise the field of energy release and reduce unproductive fuel losses. Therefore, enrichment in the first, second and tenth rings of fuel elements, counting from the centre tube of the fuel assembly, can be reduced. As a result of such profiling, the burnup depth of the most burned-out fuel elements in the cassette can be reduced to 1.015 of the average for the fuel assembly.